Image Theatre: body language and educational drama - Tomás MOTOS TERUEL (Ediciones Universidad de Salamanca, 2010)
In this paper Augusto Boal's Image Theatre is presented. It's a dramatic intervention tool based on body language, which, through the iconography made with the postures adopted by the participants, attempts to analyze a specific state of personal or collective conflict induced by a real oppression, fear or exclusion. And straight they seek collectively real alternative solution for implementing it. Then the carried out images can be dynamized through different procedures in order to create theatrical scenes. In addition, Image Theatre also can be used in education as a procedure for dynamization and encouragement to read and even as a creative, intuitive and alternative way for assessment. Image Theatre is an inclusive cross-curricular modality intervention of educational drama focused on body language, and it is also a complex confluence space of aesthetics, citizenship, ethics and psychotherapy.